BRAF V600E-Negative Hairy Cell Leukaemia - Stephen E. Langabeer; David O'Brien; Anthony M. McElligott; Michelle Lavin; Paul V. Browne (Case Reports in Hematology)
Since the initial report of the BRAF V600E mutation in hairy cell leukemia, numerous investigators have demonstrated the presence of this activating mutation in nearly all cases of this disease. A case of hairy cell leukemia is documented with a classical clinical, morphological, immunophenotypic, and cytochemical profile in which the BRAF V600E was not detected. The diagnostic and therapeutic implications are discussed.